A Study of AIF Argument Networks Anomalies and a Characterization of its Solutions - Gottifredi, Sebastián (2012)
The Argument Interchange Format (AIF) is a communal project with the purpose of developing a way of interchanging data between tools for argument manipulation and visualization. The AIF project also aims to develop a commonly agreed upon core ontology that specifies the basic concepts used to express arguments and their mutual relations. However, the flexibility provided by the AIF core ontology may lead to ambiguous or undesired interpretations. If ambiguous and anomalous situations are allowed, the purpose of using AIF as a common lingua for the research and development of argumentation systems might be jeopardized. The goal of this work is to identify anomalies that can arise and propose solutions for them.